¿Si es tan fácil salir de la trampa de la pobreza? - Sánchez Gonzalez, Jim (Perfil de Coyuntura Económica, 2009)
Reseña THE WHITE MAN’S BURDEN. Why The West’s Efforts To Aid The Rest Have Done So Much Ill And So Little Good, Easterly William, Oxford University press, 2006